Challenges of automated identification of access to education and training in Germany - Dörpinghaus, Jens [Verfasser]; Samray, David [Verfasser]; Helmrich, Robert [Verfasser] (My University, 2023)
„The German labor market relies heavily on vocational training, retraining, and continuing education. In order to match training seekers with training offers and to make the available data interoperable, we present a novel approach to automatically detect access to education and training in German training offers and advertisements and identify open research questions and areas for further research. In particular, we focus on (a) general education and school leaving certificates, (b) work experience, (c) previous apprenticeship, and (d) a list of skills provided by the German Federal Employment Agency. This novel approach combines several methods: First, we provide technical terms and classes of the education system that are used synonymously, combining different qualifications and adding obsolete terms. Second, we provide rule-based matching to identify the need for work experience or education. However, not all qualification requirements can be matched due to incompatible data schemas or non-standardized requirements such as initial tests or interviews. Although there are several shortcomings, the presented approach shows promising results for two data sets: training and retraining advertisements.“ (authors‘ abstract; BIBB-Doku)
Keywords: 370; Arbeitsmarktforschung; Stellenanzeige; Datenanalyse; Berufsklassifikation; Automatisierung